DOCTOR-PATIENT POWER RELATION: A SYSTEMIC FUNCTIONAL ANALYSIS OF A DOCTOR-PATIENT CONSULTATION - Nga, Nguyen Thanh (VNU Journal of Foreign Studies, 2017)
This paper attempts to explore the power relation between a doctor and a patient through the language they use at a consultation. The consultation is taken from YouTube. The doctor and the patient are women of different ages. The doctor is much younger than the patient. The paper uses systemic functional linguistics as the main theoretical framework, following the top-down approach to analysis; particularly from the analysis of the consultation in terms of field, tenor and mode down to the analysis of the consultation in terms of transitivity, mood and modality. The results of the analysis have revealed that behind the language the doctor and the patient used in their interaction exists social relation in which the doctor has the power over the patient.